ASSESSMENT OF THE POTENTIAL OF CULTURAL ECOSYSTEM SERVICES OF THE HRAZDAN RIVER: (analysis of the suitability of water for swimming) (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
The Hrazdan River is the largest water vein in the central part of the Republic of Armenia. It flows through the capital Yerevan and more than 60% of the country's population lives in the catchment. Thus, the study of water use opportunities is gaining both scientific and practical importance. Swimming in rivers, as a recreational activity, is one of the most valuable cultural ecosystem services. To assess its potential, a microbiological study of water was carried out in 2023, the coli index and the quantitative composition of saprophytic bacteria were determined at 16 observation points. The results show that there were no violations of the norms set for recreational water use in Solak, Argel, the upper course part of the Bjni tributary and along the course of the Marmarik tributary.
Keywords: Hrazdan River; ecosystem services; recreation; E. coli; saprophytic bacteria